A case report of small cell neuroendocrine carcinoma of the ovary and review of the literature - Ying Zhao; Fuli Kang; Xiangshu Kong; Ning Wang (Frontiers in Immunology)
Small cell neuroendocrine carcinoma of the ovary is rare pathological type with an undefined mechanism, low incidence, but high metastatic rate, high aggressiveness, and very poor prognosis, and there are no standardized treatment protocols or guidelines. In this article, we report a 48-year-old woman diagnosed with small cell neuroendocrine carcinoma of the ovary after puncture biopsy of a pelvic mass, who underwent 8 cycles of paclitaxel+carboplatin regimen chemotherapy (with the addition of the anti-angiogenesis targeted agent bevacizumab in the first 2 times, and the immunosuppressant tirilizumab in the last 2 times), followed by 12 times of tirilizumab monotherapy maintenance therapy, which was highly effective. It is believed that with newer technologies, the use of surgery, chemotherapy combined with immunotherapy, targeted therapy, genetic testing and construction of animal tumor models will play a key role in the treatment and monitoring of the prognosis of this rare disease.